Unified management of medical records as a management tool in a post-COVID center - Souza, Lara Marques (2023)
Objective: To report the experience of the members of the PET-Saúde Gestão e Assistência in the implementation of the unified management of medical records in a Post-Covid Treatment Center in the interior of Bahia. Method: This is an experience report on the experience of the tutorial group GT05 of PET-Saúde at the State University of Feira de Santana in the specialized center from August 2022 to July 2023. Results: The organization and unification activities of the medical records took place between May and July 2023, with 1.481 attendance sheets being organized in folders, with numerical coding from A01 to Z006, corresponding to the alphabetic letters from A to Z, and it was not possible to conclude, due to the end of the program's activities in the scenario of practice. The receptionists and service coordination followed the numerical coding activities of the forms to continue the organization, and the file with the users' database was made available. Conclusion: The experience of unified management of medical records allowed the members to reflect on the management tools and the importance of knowledge of the service for the implementation of resolution proposals that contribute to the organization of health management, facilitating the work of the multidisciplinary team and enabling a broader view of work processes.